Pengaruh Literasi Keuangan Syariah Dan Persepsi Masyarakat Kecamatan Pancoran Mas Kota Depok Terhadap Minat Menabung Di Bank Syariah - Taqiyuddin, Muhammad; Handoko, Luqman Hakim; Fuad, Iwan Agustiawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to determine the influence of Islamic financial literacy and public perception on interest in saving at Islamic banks. The data in this study were collected through questionnaires. This study used purposive sampling technique with a total sample of 106 respondents in Pancoran Mas District, Depok City. The method used in this research was the Partial Least Square Structural Equation Model (PLS-SEM). The results of this research show that financial literacy has a positive and significant effect on the Pancoran Mas community's interest in saving at Islamic banks. Then public perception also has a positive and significant influence on the Pancoran Mas community's interest in saving at Islamic banks.Keywords: Islamic Financial Literacy; Perception; Interest in Saving; Islamic Bank